Increased O-GlcNAcylation of NF-κB Enhances Retinal Ganglion Cell Death in Streptozotocin-induced Diabetic Retinopathy. (1st February 2016) - Kim, Seong-Jae; Yoo, Woong-Sun; Choi, Meeyoung; Chung, Inyoung; Yoo, Ji-Myong; Choi, Wan-Sung
Abstract: Purpose : Hyperglycemia results in increased flux through the hexoxamine biosynthetic pathway. We examined whether hyperglycemia increases O-GlcNAcylation in the diabetic retina and whether elevated O-GlcNAcylation of nuclear factor (NF)-κB increases apoptosis of retinal ganglion cells (RGCs) in diabetic retinopathy (DR). Materials and methods : Diabetes was induced in C57BL/6 mice by five consecutive intraperitoneal injections of 55 mg/kg streptozotocin. All mice were killed 2 months after injections and expression levels of O-GlcNAcylated proteins, O-linked N -acetylglucosamine transferase (OGT), β-d - N -acetylglucosaminidase and NF-κB, and the extent of RGC death were examined. Immunoprecipitations were performed to investigate whether O-GlcNAcylation of NF-κB led to its activation and RGC death in DR. Results : The expression levels of O-GlcNAcylated proteins and OGT were markedly higher in diabetic retinas than in control retinas. OGT colocalized with NeuN, a RGC-specific marker, and terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling-positive cells in the ganglion cell layer of diabetic retinas. The p65 subunit of NF-κB was O-GlcNAcylated and the level of O-GlcNAcylated p65 was higher in diabetic retinas than in control retinas. Conclusion : The present data suggest that hyperglycemia increases O-GlcNAcylation in DR and that O-GlcNAcylation of the p65 subunit of NF-κB is involved in hyperglycemia-induced NF-κB activation and RGC death in DR.